Search for new modulators of Phe508del-CFTR retention at the plasma membrane - Matos, Ana Margarida (2021)
Tese de doutoramento, Biologia (Biologia de Sistemas), apresentada à Faculdade de Ciências da Universidade de Lisboa, 2018